The diversity and traditional knowledge of wild edible vegetables in Aceh, Indonesia - Adnan, Adnan; Zidni Ilman Navia; Muhammad Jamil; Adi Bejo Suwardi (Ethnobotany Research and Applications, 2023)
Background: Wild edible vegetables contribute significantly to human well-being. These plants have a high nutritional value and are a source of novel alleles/genes that are important in developing new and improved crop cultivars to promote sustainable food security. However, most wild edible vegetables are less well-known and underutilized. This study aimed to investigate wild edible vegetable species diversity and their potential in the Aceh region, Indonesi Methods: The ethnobotanical study was carried out in two districs, i.e. Aceh Selatan and Aceh barat Daya. The ethnobotanical survey was carried out from May to June 2023 and included 383 randomly selected respondents. The ethnobotanical investigation uses semi-structured questionnaires to gather information on the traditional knowledge of wild edible vegetables. Plant specimens were collected and identified in Universitas Samudra. Results: A total of 86 wild species belonging to 35 families and 67 genera were documented as being consumed as vegetables by local people in the study area. In terms of frequency of citation, only 28 taxa were cited by 75% or more of the interviewed people, 17 (20%) vegetable taxa were commonly gathered and consumed, 35 (41.2%) were rarely cited - ranging from 5 to 20% of informants, and 5 were very rarely cited. Artocarpus integer, Archidendron bubalinum, Etlingera elatior, Macrothelypteris torresiana, Stenochlaena palustris, Bambusa vulgaris, Colocasia esculenta, Pseudosasa japonica, Diplazium esculentum, and Ipomoea aquatica are the ten most cited vegetables in the study area. Despite the fact that the study discovered a high diversity of wild edible vegetables, local people in Kluet Tengah only used an average of 31.11 ± 9.21 species out of 57 species recorded. Most of the reported vegetables were consumed cooked (74 species), eaten raw (2), both cooked and raw (3), and 5 species were added as a spice to the dish. Indigenous knowledge of wild edible vegetables was significantly associated with districts, age groups, and educational levels. Conclusion: Aceh has a diverse range of wild edible vegetables, but only a small proportion has been used by local people, particularly as food. Promotion and domestication of wild edible vegetables should be a primary concern in Aceh in order to take advantage of their nutritional value and potential economic value. Moreover, integrating knowledge related to wild edible vegetables into the educational curriculum is critical for educating the next generation regarding the potential of wild edible vegetables in the future. Keywords: Aceh, biodiversity, local knowledge, wild vegetable, underutilized plants Abstrak Latar Belakang: Sayuran liar memberikan kontribusi signifikan terhadap kesejahteraan manusia. Tumbuhan ini memiliki nilai gizi yang tinggi dan merupakan sumber alel/gen baru yang penting dalam pengembangan kultivar tanaman baru dan lebih baik untuk meningkatkan ketahanan pangan berkelanjutan. Meskipun demikian, sebagian besar sayuran liar kurang dikenal dan kurang dimanfaatkan. Penelitian ini bertujuan untuk mengetahui keanekaragaman sayuran liar dan potensinya di wilayah Aceh, Indonesia. Metode: Penelitian dilakukan di dua kabupaten, yaitu Aceh Selatan dan Aceh Barat Daya. Survei etnobotani dilakukan pada bulan Mei hingga Juni 2023 dan melibatkan 383 responden yang dipilih secara acak. Koleksi data etnobotani menggunakan kuesioner semi-terstruktur untuk mengumpulkan informasi tentang pengetahuan tradisional tentang sayuran liar. Spesimen tumbuhan dikumpulkan dan diidentifikasi di Universitas Samudra. Hasil: Sebanyak 86 spesies sayuran liar yang termasuk dalam 35 suku dan 67 marga ditemukan dikonsumsi sebagai sayuran oleh masyarakat lokal di lokasi penelitian. Meskipun demikian, hanya 28 taksa yang dikonsumsi oleh 75% orang atau lebih yang diwawancarai, 17 (20%) taksa sayuran yang umum dikonsumsi, 35 (41,2%) jarang dikonsumsi, dan 5 jenis sangat jarang dikonsumsi. Artocarpus integer, Archidendron bubalinum, Etlingera elatior, Macrothelypteris torresiana, Stenochlaena palustris, Bambusa vulgaris, Colocasia esculenta, Pseudosasa japonica, Diplazium esculentum, dan Ipomoea aquatica adalah sepuluh jenis sayuran yang paling banyak dimanfaatkan oleh masyarakat di lokasi penelitian. Meskipun penelitian ini menemukan keanekaragaman jenis sayuran liar yang tinggi, masyarakat lokal di Kluet Tengah hanya memanfaatkan rata-rata 31.11 ± 9.21 jenis dari 57 jenis yang ditemukan. Sebagian besar sayuran dikonsumsi dalam bentuk dimasak (74 jenis), dimakan mentah (2 jenis), dimasak dan mentah (3 jenis), dan 5 jenis ditambahkan sebagai bumbu masakan. Pengetahuan masyarakat lokal mengenai sayuran liar yang dapat dimakan berhubungan secara signifikan dengan kabupaten, kelompok umur, dan tingkat pendidikan. Kesimpulan: Aceh memiliki beragam jenis sayuran liar yang dapat dimakan, namun hanya sebagian kecil yang dimanfaatkan oleh masyarakat setempat, khususnya sebagai makanan. Promosi dan budidaya sayuran liar harus menjadi perhatian utama di Aceh untuk memanfaatkan nilai gizi dan potensi nilai ekonominya. Selain itu, mengintegrasikan pengetahuan terkait sayuran liar ke dalam kurikulum pendidikan sangat penting untuk mendidik generasi berikutnya mengenai potensi sayuran liar di masa depan. Kata kunci: Aceh, biodiversitas, pengetahuan lokal, sayuran liar, tumbuhan kurang termanfaatkan